Feminist Therapie Theory and Practice : a contemporary perspective - Ballou, Mary, ....- (New York : Springer, 2008)
In the twenty-plus years since the original Handbook of Feminist Therapy was published, members of the Feminist Therapy Institute and other forward-thinking professionals have continued to push and prod-both themselves and mainstream therapists-to examine the underpinnings of the psychotherapy endeavor. In this volume, the editors and contributors present an organized overview of the most up-to-date thinking about feminist therapy and draw attention to the alliance between feminist therapy and multicultural counseling, critical theory, and liberation psychology. Whereas most mainstream therapy models have progressed beyond a view of the therapist as an objective agent, they generally do not provide a model for understanding the therapist's and, for that matter, the client's beliefs, experiences, and world view. The contextual ecological feminist model explicated here articulates a means of examining the contextual and ecological elements of person's worlds. The authors of this volume have nicely illustrated feminist therapy's key tenets-to illuminate the multiple spheres of influence in clients' lives, to empower clients as well as ameliorate their distress, to appreciate the linkages among sociostructural, cultural and relational influences, and to work for social justice-in well-drawn theoretical explanations and carefully detailed case examples that bring us to the cutting edge of contemporary feminist therapy.
Keywords: Therapy ; feminism